Designing an Aid Device in Learning the Skill of Handstand in the Technical Gymnasium for Students - Hameed, Sanaa Khamees; Hameed, Sanaa Khamees (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to design an aid in learning the skill of handstand and learning about the effect of  using an assistive device in learning the skill of handstand in the artistic gymnastics of female students. The  assistive device consists of (2) U-shaped legs upside down, and at the end of each base post, the post can be  enlarged and zoomed out, and the bar in the middle is covered with a sponge to avoid injury. The researcher  used the experimental approach to design the two equivalent experimental groups: the experimental and the  control group, the test: pre and post, on a sample of the second stage students, the Department of Physical  Education and Sports Sciences / College of Education / Al-Farahidi University, then the researcher divided the  division (1,2) randomly by drawing lots into two groups of the control group Its number is (27) students, which  is a division (1) and the experimental group and its number is (27) students, and it is a division (2). The  research program was implemented using the assistive device. The preparatory and the closing section are the  same. The researcher concluded that adopting the designed assistant device improves the level of performance  of the skill of handstand. Where it recommended the necessity of adopting assistive devices and tools that prove  scientifically effective for learning artistic gymnastics skills to students of physical education and sports  sciences.